PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH (UKS) DI SEKOLAH DASAR NEGERI SE-KECAMATAN ALIAN KABUPATEN KEBUMEN TAHUN AJARAN 2015/2016 - Mahfud Amin Nasruloh; Endro Puji Purwono (Universitas Negeri Semarang, 2016)
The purpose of this research is to examine elementary school of Alian Kebumen district UKS program's implemented on 2015/2016 academic year. Methods of data collection using the questionnaire to take primary data and documentation to take on secondary data. Data were analyzed by using of percentage's descriptive statistical analysis. The results showed: 1) Health education: 88% with a very good category. This is showed by school already gives healthy living habit's knowledge regularly and responsible for their own health. 2) Health Care: 73% of good category. Schools have scouted the student's growth and development and gave immunization to students from related units. 3) Healthy school life's environment: 68%. This is showed by high conducive learning environment's awareness, awareness of keeping the environment of the school. It is just had limited facilities and supporting infrastructure for UKS program's implementation. It can be concluded that elementary school of Alian Kebumen district UKS program's implemented on 2015/2016 academic year goes well with an average percentage of 78%.